Executive compensation and corporate sustainability: Evidence from ESG ratings - Chen Zhu; Xue Liu; Dong Chen; Yuanyuan Yue (Heliyon, 2024)
Selecting A-share listed companies in Shanghai and Shenzhen, China, during the period of 2012–2021 as research subjects, this study examines the relationship and operational mechanisms between executive compensation and corporate ESG Ratings. It is found that executive compensation incentives can significantly enhance corporate ESG Ratings. This effect is achieved through promoting green innovation efficiency, enhancing environmental information disclosure, and improving financial performance. However, this positive impact weakens with an increase in management shareholding, but strengthens with a higher proportion of independent directors. When compensation exceeds appropriate levels, overcompensation leads to a decline in ESG Ratings. The significance of this study lies in revealing potential pathways for enhancing corporate sustainability through executive compensation incentives, while also emphasizing the importance of formulating appropriate compensation strategies.